Effect of central line bundle implementation on central line-associated bloodstream infection rates in NICU in KSA - Ratna, Amin Salim; El-Saed, Aiman; Alsaif, Saif; Tannous, Joseph; Dagunton, Nimfa; Balkhy, Hanan (International Journal of Infection Control, 2016)
Central Line-Associated Bloodstream Infections (CLABSI) remained a significant cause of mortality and morbidity in neonatal patients admitted to the neonatal ICU (NICU) who require central line insertion for whatever medical reason. Recent introduction of Central line bundle strategies was associated with a drop in the CLABSI rates. Data about the effect of central line bundle on the rate of CLABSI in neonatal patients in Saudi Arabia are lacking. In this prospective targeted surveillance study, we examined the association between central line bundle implementation and the incidence rate of CLABSI in a neonatal ICU in a tertiary teaching hospital in Saudi Arabia during the period between 2009 and 2011. We looked also at the rate of compliance with the CL bundle. The results showed a statistically significant decrease in umbilical catheter- related BSI rate (p= 0.048). Other types of central lines did not show any statistically significant association. The overall catheter utilization ratio was generally higher than that reported by the US National Healthcare Safety Network (NHSN). The overall CL bundle compliance was below the targeted rate adopted by the Institute for Healthcare Improvement (IHI). Further efforts towards increasing compliance with central line bundle strategies and reducing the use of central lines is needed to further decrease of the current rates of CLABSI in our NICU. Other factors contributing to the development of CLABSI, which were not explored in this study, need to be examined as well.